2010
DOI: 10.3233/nre-2010-0613
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal interactions in free game play of children with autism and a mobile toy robot

Abstract: Autism is a complex neuropsychological disorder characterized by qualitative alterations in social interaction and interpersonal communication. The aim of this study is to estimate the interaction between autistic children and a mobile toy robot during free spontaneous game play. The duration of different criteria including eye contact, touch, manipulation, and posture have been considered. The variety of interactions of children with autism and the mobile toy robot show that the children take an interest in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Thus, when analysing the participants’ autonomic reactions, both the Japanese and French ASD children were better synchronised with the robot than with the human. The current findings are not only similar to several data reporting that ASD children interact better with robots than with humans 29 , 30 , 32 34 , 43 , 44 , but go beyond the existing results as we demonstrated for the first time, to our knowledge, that ASD children are involved in spontaneous interpersonal synchronisation in both France and Japan. These findings can be associated with the human inclination to enact in synchrony with machines or humans without being aware of it 8 , 12 , 35 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, when analysing the participants’ autonomic reactions, both the Japanese and French ASD children were better synchronised with the robot than with the human. The current findings are not only similar to several data reporting that ASD children interact better with robots than with humans 29 , 30 , 32 34 , 43 , 44 , but go beyond the existing results as we demonstrated for the first time, to our knowledge, that ASD children are involved in spontaneous interpersonal synchronisation in both France and Japan. These findings can be associated with the human inclination to enact in synchrony with machines or humans without being aware of it 8 , 12 , 35 .…”
Section: Discussionsupporting
confidence: 91%
“…An important number of studies have shown that children with ASD better interact with animated robots than human partners using various verbal and nonverbal reactions [29][30][31][32][33][34] . Some of these studies have further demonstrated that ASD children, while engaged with a robot partner, then turn to interact with a third partner, an adult 29,30 . A recent systematic review conducted by Pennisi et al 35 confirmed that children with ASD are better encouraged in social and emotional reactions, in general, while they are in contact with animated robots than with humans.…”
mentioning
confidence: 99%
“…In this regard, previous work indicates that typical controls are capable of unambiguously differentiating their own stochastic patterns of walking movements from those of others (Johnson et al, 2012a , b ; Mistry et al, 2015 ). An open question that we can address using the present methods is whether individuals with iASD could also do that, given their reported limitations in understanding biological motions in general (Klin and Jones, 2008 ; Klin et al, 2009 , 2015 ) and generally preferring non-biological (robotics) motions instead (Giannopulu and Pradel, 2010 ; Chaminade et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, robotics studies are not included. There is an increasing amount of work in what can be called 'developmental robotics' both using models of typical development to inform robot design and learning, and designing robots for use as therapeutic aids for atypical development (Barakova et al 2009;Dautenhahn et al 2009;Farr 2010;Giannopulu 2010;Ijichi and Ijichi 2007;Wuang et al 2010). Though these are obviously technological solutions, they will not be covered here, because the work does not involve the individual interacting with a computer program in the traditional sense, because the field is still in its infancy and because the technical knowledge required to evaluate significant aspects of the work are outside the author's expertise.…”
Section: Introductionmentioning
confidence: 99%